Professional Performance Of Public High School Teachers In Sekayu City (As a Result of Strategic Planning and Principal Leadership) - Fatmawati, Fatmawati; Harapan, Edi; Rohana, Rohana (Jurnal Pendidikan Tambusai, 2021)
The purpose of this study was to determine, describe, and analyze the effect of strategic planning and principal leadership on the professional performance of public high school teachers in Sekayu City. This study used quantitative research methods through a population of 162 teachers with a sampling technique using Probability Sampling to obtain a total sample of 115 teachers. Data collection techniques used observation and questionnaires. The data analysis technique used the t test and F test. This study resulted that: 1) there was a significant influence between strategic planning on the professional performance of public high school teachers in Sekayu City by 20.3%; 2) there was a significant influence between the leadership of the principal on the professional performance of the teachers of SMA Negeri in Sekayu City of 35.9%; 3) there was a significant influence between strategic planning and principal leadership together on the professional performance of public high school teachers in Sekayu City by 39.4% and the rest was influenced by other factors.